Analysis of the Quality of Interactive Mobile Learning Media Based on Global Warming Material at SMA Negeri 2 Medan - Ezra Egidia Shelomitha Limbong; Budiman Nasution (Universitas Negeri Medan, 2025)
Student disengagement and suboptimal learning completeness in physics at SMA Negeri 2 Medan, attributed to monotonous learning media, prompted the development of a mobile learning application using MIT App Inventor to enhance student interest. This inquire about utilized the Research and Development (R&D) strategy utilized the ADDIE show with lesson X understudies as subjects. The developed media showed high validity (87.03% media, 92% material), practicality (95% teacher response, 93.8% student response), and effectiveness, as indicated by a significant N-gain of 0.80 (high category) between pre-test (46.67) and post-test (90.13) scores on global warming material. The study concludes that this mobile learning physics media is highly valid, practical, and effective for use at SMA Negeri 2 Medan. Based on this data, it can be concluded that the material physics learning media based on versatile learning MIT App Inventor created by analysts is exceptionally feasibility, exceptionally practical and exceptionally effective to utilize.